2007
DOI: 10.1007/s11740-007-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Method for optimizing the cooling design of hot stamping tools

Abstract: During the past years hot-stamped components have gained considerable importance in the automotive industry. This is due to the advantageous properties involved, such as good crash behavior and high strength. In the production of hot-stamped components the blank is rapidly cooled by the tool. This exerts an important influence on the final properties and the process time. The tool is actively cooled by cooling ducts through which a medium flows. This article will present a newly developed method in which the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…All experiments described in this work are performed on a 5-axis (three linear and two rotatory) conventional milling center rebuilt as a laser processing machine, named Kondia Aktinos 500 (Kondia, Elgoibar, Spain), whose work piece size capacity is 700 × 360 × 380 mm 3 . In addition, a high power Yb:YAG fiber laser source, Rofin FL010 (ROFIN-SINAR Laser GmbH, Bergkirchen, Germany), is used, with a maximum power output of 1 kW, emitting wavelength of 1070 nm and pulse frequency range up to 5 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments described in this work are performed on a 5-axis (three linear and two rotatory) conventional milling center rebuilt as a laser processing machine, named Kondia Aktinos 500 (Kondia, Elgoibar, Spain), whose work piece size capacity is 700 × 360 × 380 mm 3 . In addition, a high power Yb:YAG fiber laser source, Rofin FL010 (ROFIN-SINAR Laser GmbH, Bergkirchen, Germany), is used, with a maximum power output of 1 kW, emitting wavelength of 1070 nm and pulse frequency range up to 5 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the fact that nearly all mass-produced parts are manufactured employing processes that include dies and molds, directly affecting not only the efficiency of the process, but also the quality of the product [2]. Moreover, increasing demand in the automotive industry for high strength and lightweight components has led to the promotion and development of hot stamping (also known as Press Hardening) processes [3]. Through this technique, a boron steel blank is heated until austenization at temperatures between 900 • C and 950 • C inside a furnace and then transferred to an internally cooled die set, where it is simultaneously stamped and quenched.…”
Section: Introductionmentioning
confidence: 99%
“…This excellent performance of the final ANN model with an RMS error of just 7.7% for phase fraction prediction over the test dataset establishes that the final ANN model has indeed robustly learned the functional relationship between the thermal history, deformation amount and deformation temperature and the final resulting phase distribution in the boron steel. Thermal history, deformation amount and deformation temperature are the factors which have the greatest influence on the final phase distribution during tailored hot stamping and hence were used for development of the current ANN model [8,10,12,15,35,36,48,49]. There are other process parameters such as strain rate, austenitization temperature and austenitization time which also have limited influence on the final phase distribution during tailored hot stamping.…”
Section: Model Validation and Performance Analysismentioning
confidence: 99%
“…With higher cooling rates the resulting structure becomes fully martensitic, allowing higher hardness values. Steinbeiss et al [7] showed that the in hot stamping process heat transmission occurs through three factors: heat transfer between the component and the tool, heat conduction through the tool and the transfer of heat between the tool and the cooler. According to Naganathan [8] there are three ways to ensure an efficient heat transfer: use of materials with high thermal conductivity in the dies manufacturing, avoid barriers to the heat driving and improve the cooling system.…”
Section: Introductionmentioning
confidence: 99%